Development of a portable phototherapy garment (PPG) for jaundice treatment - Addi, M.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Phototherapy is the most common treatment used for jaundiced newborn by utilizing light sources such as fluorescent tubes, halogen lamp, fiberoptic system and LEDs to reduce bilirubin level in infants. Currently, the commonly used phototherapy devices in hospitals require continuous uninterrupted treatment for a period of time and generate considerable amount of heat that may lead to thermal injury to infants. Limited numbers of phototherapy devices in some developing and third-world countries have caused longer waiting periods between patients. Thus, a portable phototherapy device, which allows easy access and comfort to both infants and breastfeeding mothers, is very much preferred to overcome the current situation. The Portable Phototherapy Garment (PPG) uses blue surface mount device (SMD) LEDs which are arranged on a garment to deliver sufficient light exposure to infants in a safely manner. The PPG is also equipped with a body temperature and alert system to indicate any abnormal temperature and completion of treatment. The PPG was proven to reduce bilirubin level in artificial bilirubin standard solution (ABSS) more efficiently compared to fluorescent tubes. © 2016 IEEE.